Penganggaran di Organisasi Keagamaan: Studi Kasus pada Paroki Katedral Keuskupan Padang - Gulo, Maria Selta Kurnia Murni; Deviani, Deviani (Jurnal Eksplorasi Akuntansi, 2025)
This research was conducted to understand the budgeting and control processes in religious organizations, specifically the Cathedral Parish of the Padang Diocese. The method used in this research is qualitative through observation, interviews, and documentation. The research instrument is the researcher themselves. The research findings reveal that the budgeting process at the Cathedral Parish of Padang is still very simple and lacks standardized regulations. Budget planning is carried out at the beginning of the period through sections of each field. Control is conducted by supervising each activity, preparing accountability reports through the field section coordinators, and evaluating at the end of the period.